Local Network Security Analysis Using Intrusion Detection System (IDS) on Public Hotspot Network at Moonlight Café - Mhd Rizky Ananda Pratama Nasution; Leni Marlina; Hanna Willa Dhany (Bahasa Indonesia, 2026)
The development of computer network technology and the increasing use of public hotspot services in various public places, such as cafes, have made network security threats increasingly complex. Public hotspot networks have a high level of vulnerability to various types of cyberattacks, such as port scanning, sniffing, spoofing, brute force, and Distributed Denial of Service (DDoS). An Intrusion Detection System (IDS) is a network security solution used to detect suspicious activities and attacks on computer networks in real-time. This study aims to analyze the implementation of an Intrusion Detection System (IDS) on public hotspot networks in Moonlight Cafe to improve local network security. The research method used is an experimental method by implementing an IDS using Snort on a public hotspot network. Testing was conducted using several types of attack simulations, such as port scanning, brute force login, ping flood, and sniffing attacks. The testing parameters included the attack detection rate, response time, packet detection accuracy, false positive rate, and server resource utilization. The results showed that the IDS was able to detect various types of network attacks with an accuracy rate of 96.8%. The IDS system was also able to provide real-time notifications for suspicious activities on the public hotspot network. Based on the research results, the implementation of an IDS is proven to be effective in improving local network security within a public hotspot environment in cafes.